Dosimetric evaluation of adult and paediatric brain tumours planned using mask‐based cobalt‐60 fractionated stereotactic radiotherapy compared to linear accelerator‐based volumetric modulated arc therapy. Issue 1 (1st October 2022) - Fong, Chin Heng; Heaton, Robert; Liu, Zhihui Amy; Li, Kecheng; van Prooijen, Monique; Cho, Young‐Bin; Shultz, David B.; Tsang, Derek S.
Abstract: Introduction: We conducted a study to evaluate the dosimetric feasibility of mask‐based cobalt‐60 fractionated stereotactic radiotherapy (mcfSRT) with the Leksell Gamma Knife® Icon™ device. Methods: Eleven patients with intracranial tumours were selected for this dosimetry study. These patients, previously treated with volumetric arc therapy (VMAT), were re‐planned using mcfSRT. Target volume coverage, conformity/gradient indices, doses to organs at risk and treatment times were compared between the mcfSRT and VMAT plans. Two‐sided paired Wilcoxon signed‐rank test was used to compare differences between the two plans. Results: The V95 for PTV was similar between fractionated mcfSRT and VMAT ( P = 0.47). The conformity index and gradient indices were 0.9 and 3.3, respectively, for mcfSRT compared to 0.7 and 4.2, respectively, for VMAT ( P < 0.001 and 0.004, respectively). The radiation exposure to normal brain was lower for mcfSRT across V10, V25 and V50 compared with VMAT ( P = 0.007, <0.001 and <0.001, respectively). The median D0.1cc for optic nerve and chiasm as well as the median D50 to the hippocampi were lower for mcfSRT compared to VMAT. Median beam‐on time for mcfSRT was 9.7 min per fraction, compared to 0.9 min for VMAT ( P = 0.002). Conclusion: mcfSRT plans achieve equivalent target volume coverage, improved conformity and gradient indices, and reduced radiation doses to organs at risk as compared with VMAT plans. These results suggest superior dosimetric parameters for mcfSRT plans and can form the basis for future prospective studies. Abstract : In this comparative dosimetry study, fractionated cobalt‐60 radiosurgery plans (top panels) achieved equivalent target coverage but improved conformity and organ‐at‐risk sparing as compared to VMAT plans (bottom panels). Fractionated radiosurgery may be considered for future prospective study as a highly focused modality for photon radiation of intracranial tumours.